Geological hazard development characteristics and stability analysis of hard rock mined cavern groups: case insights from a large-scale artificial quarrying area in China - Wei, He; Wu, Shenglin; Wu, Zehui; Huang, Mengyuan; Chen, Shuping; Xu, Yunlei (Scientific reports, 2025)
Surface cavern groups formed by hard rock extraction exhibit distinct hazard-forming characteristics due to their unique genesis and geological settings, which are significantly different from those associated with underground mined-out areas. This study focuses on a typical group of abandoned artificial quarry caverns in China, where systematic engineering geological investigations and analyses of geological hazard formation mechanisms were conducted. The results indicate that the primary types of geological hazards in such caverns are overall collapse and local rockfall, with failure modes mainly including sliding, tensile cracking, toppling, and combined tensile-toppling forms. Based on field measurements of topography and the structural characteristics of the cavern group, a three-dimensional geological model was developed using ANSYS finite element software to perform stability analysis. Simulation results reveal that the arch-shaped connections between caverns and the foot zones of rock pillars are stress concentration areas, where local rock masses are subject to complex stress conditions, particularly with significant deformation responses in high-level unstable rock masses. This study contributes to a deeper understanding of the hazard development characteristics and failure mechanisms of hard rock mined-out caverns, and provides a theoretical and technical basis for geological hazard risk assessment and mitigation.